The Effect Of Visual Media On Students’ Writing Skill Of Eleventh Grade Of SMA Negeri 1 Selesai - Conny, Conny; Umara, Ummi; Yultisa, Nudia; Shella, Indry Al (BEST Journal (Biology Education, Sains and Technology), 2024)
The objective of the study is to know the significant effect of using Visual Media on students’ writing skill at the eleventh grade of SMA Negeri 1 Selesai. The method applied in this research was quantitative method in the design is Quasi experimental. Two classes were taken as the sample of the study with 20 students in each class. The classes were designed as an experimental class and controlled class. The experimental class was taught by using Visual Media while the controlled class was taught without using the treatment. The students’ population at SMA Negeri 1 Selesai, and the samples were 40 students (20 students for the experimental class and 20 students for the controlled class). The sampling technique that used was total population sampling. Moreover, this research was conducted through the following procedures giving pre-test, applying treatments, and giving post-test. The data analyzed in this research was gained through essay test. The result of the conclusion that in testing the hypothesis, the value of t-observation (to) was 8.23, and t-table (tt) at significance level of 5% was 1.686. It means tottable , then 8.23 1.686. So, the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Based on the result, it can be concluded that using Visual Media was effective on increasing students’ writing skill narrative text at the eleventh grade of SMA Negeri 1 Selesai